2018
DOI: 10.1253/circj.cj-17-0861
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Status of Smoking Inside Eating Establishments in the Cities of Kobe and Amagasaki

Abstract: The rates of recognition and implementation of the complete smoking ban were significantly lower in Amagasaki City than in Kobe City. There needs to be a strong and continuous socialization campaign to promote the ordinance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…We found more restaurants and bars which serve mainly alcohol in the "staying separate or smoking" category than in the "changing from separate smoking or smoking to no smoking" in this study. Previous studies have shown that smoking bans were more prevalent in the mainly meals than the mainly alcohol restaurants and bars [11,12], and the present study found similar results. Indoor smoking is common in bars or pubs, and owners would be concerned about the possible reduction of customers or sales that would result from an indoor smoking ban.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found more restaurants and bars which serve mainly alcohol in the "staying separate or smoking" category than in the "changing from separate smoking or smoking to no smoking" in this study. Previous studies have shown that smoking bans were more prevalent in the mainly meals than the mainly alcohol restaurants and bars [11,12], and the present study found similar results. Indoor smoking is common in bars or pubs, and owners would be concerned about the possible reduction of customers or sales that would result from an indoor smoking ban.…”
Section: Discussionsupporting
confidence: 90%
“…Indoor smoking is common in bars or pubs, and owners would be concerned about the possible reduction of customers or sales that would result from an indoor smoking ban. [13] In Japan, the mainly alcohol restaurants and bars have traditionally been regarded as places where smoking is socially acceptable [12]. It appears that voluntary smoking bans in unregulated, mainly alcohol establishments may be less aggressively promoted than other service categories.…”
Section: Discussionmentioning
confidence: 99%
“…7 ) However, this lowering effect was not observed in other districts in Hyogo Prefecture and the difference was linked to significantly higher rates of recognition and compliance with the smoking ban among residents of Kobe-city where a prefectural government office is located. 8 However, most of the previous studies were on the short-term effects (i.e., within 3 years after the enactment of smoking ban legislation in public places) and the long-term effect has not been established. Therefore, this research was designed as a long-term follow-up of ACS hospitalizations under Hyogo-L from 2013 to 2019 using a large real-world administrative database to define whether the ACS reduction in Kobe-city and nonreduction in other areas has continued and whether the reducing effect in Kobe-city is different for patients with and without ACS risk factors such as smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using questionnaires revealed that adherence and recognition to Hyogo-L in bars and restaurants were higher in Kobe-city than in Amagasaki-city in the Hanshin district with a significant difference. 8 As a result, the higher compliance with Hyogo-L in Kobe-city may have contributed to the long-term differences between Kobe-city and other districts. Also, this shows the significance of compliance and recognition among residents of smoking ban legislation with partial restrictions.…”
Section: Discussionmentioning
confidence: 99%